Peran Pemerintah dalam Mengatasi Cyberbullying di Media Sosial pada Anak di Usia Muda - Muhamad Badru Salam; Adie Dwiyanto Nurlukman; Amiludin Amiludin; Irwandi Irwandi (Universitas Medan Area, 2021)
Cyberbullying in cyberspace involves a variety of behavioral risks, including bullying and provoking hostility on the internet. This study aims to determine the involvement of children at a young age on social media as victims of cyberbullying cases, as well as the role of the government in efforts to reduce cases of victims of abuse on social media so that it will decrease. The method used in this study uses qualitative research in the form of literature review with systematic mapping study techniques using secondary data such as reports and documents related to research. The results of this study indicate that the factors of social support are very influential for children because the origin of sexual violence or sexual harassment on social media is from the closest people doing social activities with children and how the family practices good parenting, monitoring how children get along with people. another, household harmony is very influential on children.